Faktor-faktor yang Mempengaruhi Pendapatan Petani Beras Hitam Di Kecamatan Waluran Dan Ciemas - Dimyati Dimyati; Neneng Kartika Rini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2019)
The income referred to from this research is the results generated from the farming process. The study aimed to determine the effect of land area, seeds, fertilizers, pesticides, capital, labor, selling prices, production on the income of black rice farmers in the Districts of Waluran and Ciemas. The method used in this research is a quantitative descriptive method. Respondents related to this research were black rice farmers in Waluran and Ciemas sub-districts, as many as 81 respondents. Based on multiple linear calculations simultaneously the -7 variables significantly affected the income of black rice farmers, while partially from the -7 variables only 4 influential variabl es include land area: fertilizer, seeds, production. While the capital, labor, and selling prices have no significant effect on the income of black rice farmers in Waluran and Ciemas sub-districts.